Imagens projetadas: projeções audiovisuais e narrativas no contexto da arte contemporânea - Cruz, Roberto Moreira S. (2011)
This thesis specifically addresses the concept of expanded cinema for the analysis of works which use multiprojections. Review authors as Raymond Bellour, Philippe Dubois, Dominique Paini, Anne Marie Duguet, among others, underlining the approach presented by Gene Youngblood in his book Expanded Cinema (1970). Locate in the historical context of the 1960s until nowadays, cinematographic and videographic experiments that suggested expressive and relevant modes to this definition, working sounds and projected images and their relation with the exhibition space and the viewer. Specifically considers the narrative possibilities observed in filminstallations and audiovisual performances. It analyzes the peculiarities of these formas of display, in relation to proposal narratives in which the enunciation of films establishes a clear correlation with the time of projection. The thesis also presents a specific report on the international exhibition Cinema Sim- Narrativas e Projeções, help by Itau Cultural in 2008, curated by Roberto Moreira S. Cruz. This exhibition was a milestone in the development process throughout the study. Demanded a review of the recent audiovisual productions is within the context of contemporary art